BUILDING A CIVILIZED DIGITAL CIVILIZATION: THE URGENCY OF ISLAMIC VALUES FOR THE YOUNG MUSLIM GENERATION IN THE 5.0 ERA - Taufik Hidayat (RADJA PUBLIKA, 2025)
The advancement of digital technology in the modern era has brought about significant changes in ways of thinking, behaving, and interacting, particularly among the younger generation. The rapid flow of global information is often unfiltered by moral and spiritual values, potentially distancing the younger generation from the true teachings of Islam. In this context, instilling Islamic values is crucial to ensure that the use of digital technology remains within the bounds of Islamic law and good morals. This study aims to outline the concept and strategy for instilling Islamic values in the use of digital media, based on the perspectives of the Qur'an, Hadith, and the thoughts of Islamic scholars. The research method employed a qualitative approach through a literature review of relevant Islamic literature. The study's results indicate that values such as piety, trustworthiness, iffah (maintaining honor), tabligh (conveying the truth), and mas'uliyyah (responsibility) must be the foundation of digital ethics for the younger generation. Through Islamic education, parental role models, and the development of a healthy social and virtual environment, these values can be internalized, enabling digital technology to become a means of preaching, education, and strengthening faith. Thus, instilling Islamic values is not only a moral bulwark, but also a direction for the younger generation to utilize digital progress in a civilized, productive manner, and in accordance with Islamic guidance.